A flower-like waterborne coating with self-cleaning, self-repairing properties for superhydrophobic applications - Xinyu Wu; Feng Yang; Jian Gan; Wanying Zhao; Yan Wu (Journal of Materials Research and Technology, 2021)
A durable waterborne coating with superhydrophobic function has great application in construction, wooden furniture, vehicles, electronic instruments, and leather finishes. Here, we exploit a facile and scalable strategy for constructing durable wood products with superhydrophobic, self-cleaning, and self-repairing properties through a microencapsulation approach, which includes sodium dodecylbenzene sulfonate as a carrier, polytetrafluoroethylene (PTFE) as wall material, and vinyl triethoxy silane (VTES) as core material. The superhydrophobic character is attributed to the –CH3 in stearic acid molecules that successfully grafted onto zinc acetate to generate zinc stearate (ZnSt2), forming a micron flower-like arrayed on the surface of the wood. Combining an uncomplicated immersion and heat treatment route, the collapsed coating can be recovered and the surfaces with the superhydrophobic structure can be regained. This durable coating strategy has high application value in many fields, for instance, wooden furniture, wooden structure buildings, and the protection of historic sites.